Intelecção e interpretação : uma articulação necessária para a compreensão dos enunciados matemáticos - Lavigne, Thatiana Almeida (2015)
The aim of this study is to analyze the formulations set out on mathematical textbooks designed for fifth grade in order to identify and to diagnose elements and possible factors that may hinder or mislead the understanding and interpretation of mathematical formulations set out, which can cause an inadequate mental representation, thereby undermining the reflective capacity of students. To that end, we carried out a field survey with fifty-two (52) teachers in training in order to diagnose the construct of these enunciations. It is assumed that the textual construction of the set out, that is the structure of the language and the words, should be made and submitted to the student/reader so that they would understand them clearly, as well as respond to them with autonomy in the absence of a teacher. Were chosen textbooks of Mathematics on the basis of the methodological approach of Discursive Textual Analysis, which works with meanings constructed from a set of texts in order to achieve a description and interpretation of some senses the reading can inspire. In this way, the study emphasizes not only the importance of contextualizing the content to assist and facilitate the understanding of mathematical statements that can influence and interfere with the learning process of students, but, also, the use of a clear and explicit language necessary for a correct understanding and interpretation of the student/reader. Therefore, on the basis of the factors analyzed, were identified that the difficulty to interpret and understand the mathematical statements are associated with the language used by the authors of the textbook, by omission of information or for presenting ambiguity and polysemy. In this sense this research proposes a reflection and invites the professionals of education, both, educators and authors of textbooks to (re) think about the form of the preparation and construction of these formulated set out, so that they observe attentively the juxtaposed elements or the absence of them, without which the student/reader can not understand what he reads due to the deficit in the structure of the formulated set outs.